2014
DOI: 10.1016/j.tiv.2014.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of in vitro nanoparticle toxicity – The case of poly(amido amine) dendrimers

Abstract: A phenomenological rate equation model is constructed to numerically simulate nanoparticle uptake and subsequent cellular response. Polyamidoamine dendrimers (generations 4-6) are modelled and the temporal evolution of the intracellular cascade of; increased levels of reactive oxygen species, intracellular antioxidant species, caspase activation, mitochondrial membrane potential decay, tumour necrosis factor and interleukin generation is simulated, based on experimental observations. The model serves as a tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 52 publications
3
55
1
Order By: Relevance
“…According to the description of "Operational models of pharmacological agonism" by Black and Leff (Black and Leff, 1983), the action is one of a partial agonist, and IC 50 represents the concentration at which half the maximum observed affect is elicited. A clear dose dependence is observable, and, as illustrated in Table 1, the IC 50 value decreases with increasing exposure time, indicative of a progressive toxic response, as, for example, experimentally demonstrated and numerically simulated using a phenomenological rate equation approach by Maher et al (2014), for the in vitro response to Poly (amido amide) (PAMAM) dendrimer exposure. Figure 3 shows the equivalent cytotoxic response for HeLa cells on the collagen matrices.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…According to the description of "Operational models of pharmacological agonism" by Black and Leff (Black and Leff, 1983), the action is one of a partial agonist, and IC 50 represents the concentration at which half the maximum observed affect is elicited. A clear dose dependence is observable, and, as illustrated in Table 1, the IC 50 value decreases with increasing exposure time, indicative of a progressive toxic response, as, for example, experimentally demonstrated and numerically simulated using a phenomenological rate equation approach by Maher et al (2014), for the in vitro response to Poly (amido amide) (PAMAM) dendrimer exposure. Figure 3 shows the equivalent cytotoxic response for HeLa cells on the collagen matrices.…”
Section: Discussionmentioning
confidence: 88%
“…The dose dependent response of toxicity assays has been comprehensively described in the treatment by Black and Leff (Black and Leff, 1983) and, more recently, the phenomenological rate equation model of Maher et al (2014) demonstrated that the dose and time dependent responses can be reproduced by consideration of a complex cascade of events from the uptake of the external agent, to the registration of the cellular response by the cytotoxicological assay. The response profile is sensitive to the uptake rate, cellular reactions and the assay responses.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria exist within the cells in all stages of their DNA replication, and are first targeted by DOX which explains its earlier response and higher sensitivity. [45][46][47] Since cells will be analysed after 24 h exposure, the IC 50 determined using the MTT assay was used for the rest of the study.…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%
“…The effect of PAMAM dendrimer generation on their cytotoxicity was also investigated using an in vitro experiment that examined high-generation (G4, G5, and G6) PAMAM dendrimers (Mukherjee et al, 2010a(Mukherjee et al, , 2010bMaher et al, 2014). However, the wide range of PAMAM generations was not examined yet to elucidate the relationship between their generations and cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%